Why do people purchase from online travel agencies (OTAs)? A consumption values perspective - Shalini Talwar; Amandeep Dhir; Puneet Kaur; Matti Mäntymäki (Elsevier, 2022)
Online travel agencies (OTAs) are struggling to remain financially sustainable due to intense competition. To overcome this challenge, OTAs need to better engage their customers by offering them superior value propositions. This calls for an in-depth understanding of the consumption values pertinent to the OTA context. To address this gap, the current study puts forward a framework for predicting purchase intention by adapting the theory of consumption values to the OTA context. The proposed model is tested with data collected from 809 OTA users. The results imply that quality-of-benefits, monetary, social status, preference, and information values predict purchase intention toward OTAs, with the chief driver being the quality-of-benefits value, followed by the preference value. Moderation analysis further reveals that the strength of the relationship between these values and purchase intention differs between users in different age groups and between users with different levels of privacy and security concerns, hygiene consciousness, and visibility perceptions.